Consensus‐based clinical recommendations and research priorities for anticoagulant thromboprophylaxis in children hospitalized for COVID‐19–related illness. (29th October 2020) - Goldenberg, Neil A.; Sochet, Anthony; Albisetti, Manuela; Biss, Tina; Bonduel, Mariana; Jaffray, Julie; MacLaren, Graeme; Monagle, Paul; O'Brien, Sarah; Raffini, Leslie; Revel‐Vilk, Shoshana; Sirachainan, Nongnuch; et al.
Abstract: Background: Observational studies indicate that children hospitalized with COVID‐19‐related illness, like adults, are at increased risk for venous thromboembolism (VTE). A multicenter phase 2 clinical trial of anticoagulant thromboprophylaxis in children hospitalized with COVID‐19‐related illness has recently been initiated in the United States. To date, there remains a paucity of high‐quality evidence to inform clinical practice world‐wide. Therefore, the objective of this scientific statement is to provide consensus‐based recommendations on the use of anticoagulant thromboprophylaxis in children hospitalized for COVID‐19‐related illnesses, and to identify priorities for future research. Methods: We surveyed 20 pediatric hematologists and pediatric critical care physicians from several continents who were identified by Pediatric/Neonatal Hemostasis and Thrombosis Subcommittee leadership as having experience and expertise in the use of anticoagulant thromboprophylaxis and/or the management of COVID‐19‐related illness in children. A comprehensive review of the literature on COVID‐19 in children was also performed. Results: Response rate was 90%. Based on consensus of expert opinions, we suggest the administration of low‐dose low molecular weight heparin subcutaneously twice‐daily as anticoagulant thromboprophylaxis (in the absence of contraindications, and in combination with mechanical thromboprophylaxis with sequential compression devices, where feasible) in children hospitalized for COVID‐19‐related illness (including the multisystem inflammatory syndrome in children [MIS‐C]) who have markedly elevated D‐dimer levels or superimposed clinical risk factors for hospitalassociated VTE. For children who are clinically unstable or have severe renal impairment, we suggest the use of unfractionated heparin by continuous intravenous infusion as anticoagulant thromboprophylaxis. In addition, continued efforts to characterize VTE risk and risk factors in children with COVID‐19, as well as to evaluate the safety and efficacy of anticoagulant thromboprophylaxis strategies in children hospitalized with COVID‐19‐related illness (including MIS‐C) via cooperative multicenter trials, were identified among several key priorities for future research. Conclusion: These consensus‐based recommendations on the use of anticoagulant thromboprophylaxis in children hospitalized for COVID‐19‐related illnesses and priorities for future research will be updated as high‐quality evidence emerges.